Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 1 - Functions and Limits - Review - Exercises - Page 96: 3



Work Step by Step

Given $f(x) = x^{2}-2x+3$ $\frac{f(a+h)-f(a)}{h} = \frac{(a+h)^{2}-2(a+h)+3-(a^{2}-2a+3)}{h} = \frac{a^{2}+2ah+h^{2}-2a-2h+3-a^{2}+2a-3}{h} = \frac{2ah+h^{2}-2h}{h} = 2a+h-2 = 2a-2+h$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.